Order Placement in a Continuous Double Auction Agent Based Model - Alexandru Mandes (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
Modeling intraday financial markets by means of agent based models requires an additional building block which reflects the order execution, i.e. the trading process. Current implementations rely only on stochastic placement strategies, ranging from total randomness to adding some budget constraints. This contribution addresses the issue of order placement for low-tech traders, by replacing the zero-intelligence assumption with a microtrading-based approach. The results show that the power-law decaying relative price distribution of off-spread limit orders and the concave shape of the overall market price impact can be replicated when rational order submission strategies are used.
Keywords: C63; N20; 330; agent based modeling; high-frequency financial markets; continuous double auction; order placement; market impact